2017
DOI: 10.1021/acssynbio.6b00250
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Translation Is More Variable than Transcription

Abstract: Although RNA synthesis can be reliably controlled with different T7 transcriptional promoters during cell-free gene expression with the PURE system, protein synthesis remains largely unaffected. To better control protein levels, we investigated a series of ribosome binding sites (RBSs). Although RBS strength did strongly affect protein synthesis, the RBS sequence could explain less than half of the variability of the data. Protein expression was found to depend on other factors besides the strength of the RBS,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 49 publications
3
53
0
Order By: Relevance
“…Having identified that translation initiation is inefficient in PUREfrex, we next attempted to improve this process. We first hypothesized that translation initiation is hampered by mRNA secondary structures (58,(77)(78)(79)(80) that would be more susceptible to form in vitro due to poor coupling between transcription and translation. In E. coli, the first ribosome translating an mRNA often closely follows the transcribing RNA polymerase (see Castro-Roa and Zenkin (81) for an in vitro study with the endogenous E. coli RNA polymerase).…”
Section: Attempts To Restore Transcription-translation Coupling Failementioning
confidence: 99%
“…Having identified that translation initiation is inefficient in PUREfrex, we next attempted to improve this process. We first hypothesized that translation initiation is hampered by mRNA secondary structures (58,(77)(78)(79)(80) that would be more susceptible to form in vitro due to poor coupling between transcription and translation. In E. coli, the first ribosome translating an mRNA often closely follows the transcribing RNA polymerase (see Castro-Roa and Zenkin (81) for an in vitro study with the endogenous E. coli RNA polymerase).…”
Section: Attempts To Restore Transcription-translation Coupling Failementioning
confidence: 99%
“…In a typical diluted in vitro environment, system stochasticity is often omitted due to the assumption that, under a well-stirred bulk environment, a low concentration of molecules and the random nature of their collisions can be eliminated, or at least greatly reduced [93]. However, the minimal CFPS system PURE hosts more than 900 reactions and involves the translation process [94], without considering the whole transcription process [95]. Therefore, this intrinsic randomness of the CFPS system cannot be completely ignored in micro-compartments, even under bulk conditions.…”
Section: Stochasticitymentioning
confidence: 99%
“…Stochasticity due to the low concentration of molecules and the random nature of their collisions can be eliminated, or at least greatly reduced, via stirring . However, as indicated above, even with the most simplified CFPS system PURE, there would be more than 968 reactions in total, not even considering the whole transcription process involve both binding of RNA polymerase as well as the folding of mRNA . Therefore, this intrinsic randomness could not be completely ignored in microcompartments, perhaps even under bulk conditions.…”
Section: The Impact Of Stochasticitymentioning
confidence: 99%